1978
DOI: 10.1119/1.11298
|View full text |Cite
|
Sign up to set email alerts
|

What the electromagnetic vector potential describes

Abstract: An explicit physical interpretation of the electromagnetic vector potential is here pointed out—as field momentum available for exchange with kinetic momenta of charged matter. It is shown that the vector potential can be quite as directly measurable, without recourse to only quantum-mechanical effects, as are scalar potential differences and the force fields E, B. This suggests, in keeping with quantum electrodynamics, that the equations for potentials may be regarded as more ’’basic’’ than the Maxwell equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
12

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 0 publications
2
76
0
12
Order By: Relevance
“…Holding an opposite view are Heaviside and Hertz who envisaged the vector potential as merely an auxiliary artifact to computation (see Refs. [27][28][29][30][31][32][33][34]). The physicality of the vector potential is now well proven experimentally [35] and it was shown that in certain well-defined situations are measurable and possess a topology transforming according to the SU(2) group [36].…”
Section: The Electromagnetic Origin Of Inertiamentioning
confidence: 98%
“…Holding an opposite view are Heaviside and Hertz who envisaged the vector potential as merely an auxiliary artifact to computation (see Refs. [27][28][29][30][31][32][33][34]). The physicality of the vector potential is now well proven experimentally [35] and it was shown that in certain well-defined situations are measurable and possess a topology transforming according to the SU(2) group [36].…”
Section: The Electromagnetic Origin Of Inertiamentioning
confidence: 98%
“…For example, an atomic mass defect is expressible in terms of the Coulomb potential. Similarly, momentum balance selects the magnetic gauge, as Konopinski (7) and others have argued.…”
Section: Introductionmentioning
confidence: 93%
“…Visivelmente o termo m r v + (q/c) r A faz agora o papel de momento da carga e no tratamento Hamiltoniano será o momento canônico, que por sua vez se transformará em -ih∇/2π no tratamento do efeito Aharonov-Bohm. Konopinski [12] chama o termo (q/c) r A de estoque de momento de campo à disposição da carga (store of field momentum available to the charge) porque na ausência de gradientes no lado direito da Eq. 25, o lado esquerdo é análogo ao da equação de variação da energia cinética …”
Section: T Qu Q C a Vunclassified